Evaluation of the antimicrobial activity of natural extracts upon wine spoilage microorganisms - Pereira, M. F. (2015)
The present work evaluated the activity of Vaccinium corymbosum, Prunus cerasus and Quercus ilex aqueous extracts against the wine spoilage yeasts Dekkera/Bretanomyces. Minimum Inhibitory Concentrations (MIC) and Minimum Lethal Concentrations (MLC) were determined for several strains and time-death assays, for the most active extracts, were performed. The results showed that among all extracts only V. corymbosum fruit decoction and P. cerasus fruit infusion exhibited antimicrobial activity, with MLC values of 200 and in the range 300-500 mg/mL, respectively. Time-death curves were performed for V. corymbosum fruit decoction, with a significant viable cell count reduction of 4-5 log cycles in 48 hours being attained.